Commuter spouses : new families in a changing world - Lindemann, Danielle J. (ILR Press, an imprint of Cornell University Press, 2019)
"Commuter spouses--married couples who live apart due to the demands of their dual professional careers--shed light on a series of broad shifts in the dynamics of marriage, family, gender roles, and professional careers in the United States"--